Disciplina judicial y ética de los jueces: algunas controversias y propuestas - Steidel Figueroa, Sigfrido (2023)
Judicial ethics has become prominent again among topics discussed in Ibero-America, even if ethics has a long history as a field within philosophy. The way in which judicial ethics has been dealt with by Spanish and Latin American courts has not been uniform. Some countries in the region have adopted codes of ethics that pretend to guide judicial behavior independently from disciplinary regulations that bind judges. In this context, the rise of Ethics Commissions or Tribunals is a new development that poses interesting questions to which answers are still incipient. In this ar ticle, the author presents some of these controversies. The author identifies three variants existing in Ibero-America with regard to the way to regulate judicial behavior, and considers complaints raised against each, analyzes their characteristics, and presents so me advantages and disadvantages associated with each model.